Schottky barrier parameters and low frequency noise characteristics of graphene-germanium Schottky barrier diode - Khurelbaatar, Zagarzusem; Kil, Yeon-Ho; Shim, Kyu-Hwan; Cho, Hyunjin; Kim, Myung-Jong; Lee, Sung-Nam; Jeong, Jae-Chan; Hong, Hyobong; Choi, Chel-Jong (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2016)
We investigated the electrical properties of chemical vapor deposition-grown monolayer graphene/n-type germanium (Ge) Schottky barrier diodes (SBD) using current-voltage (I-V) characteristics and low frequency noise measurements. The Schottky barrier parameters of graphene/n-type Ge SBDs, such as Schottky barrier height (Phi(B)), ideality factor (n), and series resistance (R-s), were extracted using the forward I-V and Cheung's methods. The Phi(B) and n extracted from the forward In(I)-V plot were found to be 0.63 eV and 1.78, respectively. In contrast, from Cheung method, the Phi(B) and n were calculated to be 0.53 eV and 1.76, respectively. Such a discrepancy between the values of Phi(B) calculated from the forward I-V and Cheung's methods indicated a deviation from the ideal thermionic emission of graphene/n-type Ge SBD associated with the voltage drop across graphene. The low frequency noise measurements performed at the frequencies in the range of 10 Hz-1 kHz showed that the graphene/n-type Ge SBD had 1/f(gamma) frequency dependence, with gamma ranging from 1.09 to 1.12, regardless of applied forward biases. Similar to forward-biased SBDs operating in the thermionic emission mode, the current noise power spectral density of graphene/n-type Ge SBD was linearly proportional to the forward current. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: JUNCTION; CONTACT